Stress and cortisol levels among members of the nursing team - Vanessa Augusto Bardaquim; Sérgio Valverde Marques dos Santos; Ernandes Gonçalves Dias; Rita de Cássia de Marchi Barcellos Dalri; Aida Maria de Oliveira Cruz Mendes; Maria Cecília Gallani; Maria Lúcia do Carmo Cruz Robazzi
ABSTRACT Objective: To analyze the characteristics of hospital nursing professionals with the presence of stress, and to associate this with capillary cortisol. Method: A cross-sectional, exploratory and correlational study, conducted in a hospital in São Paulo, Brazil. A total of 164 nursing professionals participated; the Perceived Stress Scale was administered, and hair samples were obtained for laboratory analysis. Data were entered into a Microsoft Excel spreadsheet (2010), and then into Microsoft Office and the R software, version 3.2.2. Results: High levels of capillary cortisol in 47% of participants suggest the presence of stress, but no statistical significance between cortisol and stress levels were found. Conclusions: Stress and capillary cortisol levels were indicative of stress among nursing professionals; however, no association between them was found, although the values found were above those recommended.